1983
DOI: 10.1136/gut.24.11.1020
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic dilatation in achalasia.

Abstract: SUMMARY To assess the value of pneumatic dilatation of the cardia, 63 patients with achalasia have undergone a total of 107 Rider-Moeller dilatations over the last six years. There was a marked improvement in swallowing immediately after dilatation in all but two patients, there were no deaths attributable to the procedure and serious complications were rare (1.6% of patients). The first 50 cases have been followed from nine to 73 months after their initial dilatation (mean follow-up 29.7 months).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(37 citation statements)
references
References 11 publications
2
34
0
1
Order By: Relevance
“…It seems likely that no single therapeutic technique will be found to be optimal for all patients with achalasia. Our findings extend those reported earlier [2] that pneumatic di latation is significantly more effective in the elderly than in the younger patient. Although oesophageal dilatation is commoner in the older patients, relief from pneumatic dilata tion is not explicable on this basis.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It seems likely that no single therapeutic technique will be found to be optimal for all patients with achalasia. Our findings extend those reported earlier [2] that pneumatic di latation is significantly more effective in the elderly than in the younger patient. Although oesophageal dilatation is commoner in the older patients, relief from pneumatic dilata tion is not explicable on this basis.…”
Section: Discussionsupporting
confidence: 81%
“…Elderly patients present prob lems in management, and an earlier study suggested that pneumatic dilatation of the cardia may be particularly effective in this age-group [2]. This paper presents the long-term results of pneumatic dilatation for achalasia over an 11-year period, examined in relation to age and other factors of possible prognostic sig nificance.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, advanced age, a moderately dilated esophagus and a long history of symptoms prior to diagnosis were all found to predict a favorable treatment result [14,[25][26][27] , whereas male gender was found to predict a poor outcome [15] . However, the most significant factor predicting response to treatment appears to be the age at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…28 The mean delay in diagnosis is 5 years (range, 2-7 years). [29][30][31][32][33][34][35] Howard et al 36 reported that 36.8% of achalasia patients had been treated for GERD. Additionally, Rosenzweig and Traube 9 showed that the initial diagnosis was achalasia in only 12 of out 25 achalasia patients, whereas the other 13 patients were diagnosed incorrectly.…”
Section: Attributing Factors For Diagnostic Delay In Achalasiamentioning
confidence: 99%